Arabic Speaking Skill Learning Using the Experiential Learning Theory-Based Learning Model and Its Role in Learning Model Development | taʿlīm mahārat al-kalām ʿalā ḍaw - Sulton Firdaus (Universitas Islam Negeri Palangka Raya, 2024)
The objectives of this study encompass identifying activities that enhance speaking skills, providing a learning model grounded in experiential learning theory, and assessing its effectiveness. At the Centre for Foreign Language Development, speaking skill training involves activities like debating, delivering speeches, storytelling, discussing, writing, and translating, while at Darullughah Wadda